Increasing efficiency of enzymatic hemicellulose removal from bamboo for production of high-grade dissolving pulp. (January 2017) - Zhao, Lingfeng; Yuan, Zhaoyang; Kapu, Nuwan Sella; Chang, Xue Feng; Beatson, Rodger; Trajano, Heather L.; Martinez, D. Mark
Highlights: Sequential refining-xylanase treatment upgraded bamboo dissolving pulp. Mechanical refining improved the accessibility of xylan to enzymes. Combined refining-xylanase treatment improved delignification during bleaching. Proposed process increased reactivity and brightness of the final pulp. Abstract: To improve the efficiency of enzymatic hemicellulose removal from bamboo pre-hydrolysis kraft pulp, mechanical refining was conducted prior to enzyme treatment. Refining significantly improved the subsequent hemicellulose removal efficiency by xylanase treatment. Results showed that when PFI refining was followed by 3 h xylanase treatment, the xylan content of the bamboo pre-hydrolysis kraft pulp (after first stage oxygen delignification) could be decreased to 2.72% (w/w). After bleaching of enzyme treated pulp, the alpha-cellulose content was 93.4% (w/w) while the xylan content was only 2.38%. The effect of refining on fibre properties was investigated in terms of freeness, water retention value, fibre length and fibrillation characteristics. The brightness, reactivity and viscosity were also determined to characterize the quality of final pulp. Results demonstrated the feasibility of combining refining and xylanase treatment to produce high quality bamboo dissolving pulp.